2014
DOI: 10.1007/s00455-014-9580-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Chin-Down and Chin-Tuck Maneuver on the Swallowing Kinematics of Healthy Adults

Abstract: The purpose of the study was to investigate the influence of the chin-tuck maneuver on the movements of swallowing-related structures in healthy subjects and formulate standard instructions for the maneuver. A total of 40 healthy volunteers (20 men and 20 women) swallowed 10 mL of diluted barium solution in a “normal and comfortable” position (NEUT), a comfortable chin-down position (DOWN), and a strict chin-tuck position (TUCK). Resting state anatomy and kinematic changes were analyzed and compared between po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 27 publications
1
44
0
2
Order By: Relevance
“…VFSS is also useful to evaluate the effects of adaptive swallowing methods, such as the chin‐tuck maneuver, the supraglottic swallow, and the effortful swallow. Given that the presence of pharyngeal residue is the most common finding in SBMA patients and a laryngeal penetration risk exists even in those without subjective dysphagia, we recommend the chin‐tuck maneuver and the effortful swallow as safe methods of swallowing for all SBMA patients with dysphagia 36, 37. We also reported that a 6‐week head lift exercise may improve swallowing dysfunction as measured by tongue pressure 38.…”
Section: Discussionmentioning
confidence: 92%
“…VFSS is also useful to evaluate the effects of adaptive swallowing methods, such as the chin‐tuck maneuver, the supraglottic swallow, and the effortful swallow. Given that the presence of pharyngeal residue is the most common finding in SBMA patients and a laryngeal penetration risk exists even in those without subjective dysphagia, we recommend the chin‐tuck maneuver and the effortful swallow as safe methods of swallowing for all SBMA patients with dysphagia 36, 37. We also reported that a 6‐week head lift exercise may improve swallowing dysfunction as measured by tongue pressure 38.…”
Section: Discussionmentioning
confidence: 92%
“…16 Postural changes, such as chin down (positioning the chin to the chest) or head turn (turning head over right or left shoulder), have been shown to change the biomechanics and pressure generation during swallowing and to reduce the occurrence of aspiration, depending on the swallow impairments present. [17][18][19][20][21] Additionally, swallowing maneuvers, such as the effortful swallow, also impact swallowing physiology and may have positive effects on pharyngeal pressure generation.…”
Section: Compensatory Techniquesmentioning
confidence: 99%
“…[26]. This minimizes the vertical distance and increases the maximum acceleration of the hyoid bone [5], reducing both swallowing duration and iEMG.…”
Section: Cervical Joint Anglementioning
confidence: 99%
“…Chin-up posture extends the suprahyoid muscle as well as opening the larynx. Therefore, even in healthy individuals, swallowing while in the chin-up posture increases the movement distance and decreases the maximum acceleration of the hyoid bone [5]. As a result, in healthy individuals, swallowing duration is prolonged and integrated electromyography (iEMG) of suprahyoid muscles is increased [6].…”
Section: Introductionmentioning
confidence: 99%